2016
DOI: 10.1177/0170840615613372
|View full text |Cite
|
Sign up to set email alerts
|

The Enabling and Constraining Effects of Social Ties in the Process of Institutional Entrepreneurship

Abstract: While the past decade has produced a number of insights into the process of institutional change, scholars still lack a comprehensive understanding of the germinal stages of institutional entrepreneurship. More specifically, further knowledge is needed into what factors cause certain individuals to initiate norm-breaking behaviour while others continue to adhere to societal expectations. Prior work seeking to inform this question has focused either on individual-level or environmental-level explanations. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 73 publications
0
50
1
1
Order By: Relevance
“…The conditions of agency cannot be reduced to the position of power in a network -for instance, as a field broker or member of an elite, preferably in a heterogeneous field. Qureshi et al (2016) perfectly illustrate this point when they demonstrate that the dynamic use of a network is a strong determinant that an agency can lead to social change. There is much to learn about how agency not only emerges from a position in a network but also can be revealed by the microanalysis of the network foundation of agency.…”
Section: Implications For Researchmentioning
confidence: 84%
“…The conditions of agency cannot be reduced to the position of power in a network -for instance, as a field broker or member of an elite, preferably in a heterogeneous field. Qureshi et al (2016) perfectly illustrate this point when they demonstrate that the dynamic use of a network is a strong determinant that an agency can lead to social change. There is much to learn about how agency not only emerges from a position in a network but also can be revealed by the microanalysis of the network foundation of agency.…”
Section: Implications For Researchmentioning
confidence: 84%
“…Here, Homans (1958) argued that cohesiveness, a property that attracts people to take part in a group, is a value that draws social approval and rewards to that group. The ties that exist among individuals engaged in social exchanges affect their actions, including their willingness to adhere to or violate social norms (Qureshi, Kistruck and Bhatt, 2016). The norm of reciprocity allows for individuals to be more trusting of, and committed to, one another (Cropanzano and Mitchell, 2005).…”
Section: Set and The Individual Within A Team Contextmentioning
confidence: 99%
“…Zafeiropoulou and Koufopoulos (2013) utilised social network theory to explore the development of social franchising within social enterprise and identified that relational network embeddedness and relationship development characterised by trust, reduced conflict, collaboration, reduced power dynamics and flexibility were crucial to the development and performance of social franchises. Qureshi et al (2016) utilised social network theory to understand the development of social entrepreneurship in China and identified that those entrepreneurs that had more pluralistic social networks were more likely to reject conformism and act innovatively. Smith and Stevens (2010) explored how geographic space and the scope and reach of the social enterprise affected levels of embeddedness, engagement with social networks and hence shaped social entrepreneur behaviour and actions.…”
Section: Conceptualising Social Enterprise Ecosystems Using Evolutionmentioning
confidence: 99%
“…There is also a significant strand of research that argues that informal institutions such as culture, heritage, and normative values are significant factors in shaping economic behaviour (Baumol, 1990;North, 1990;Williamson, 2000;Puumalainen et al, 2015); furthermore, these informal institutions are shaped by social networks that mediate trust, reputation, collaboration, power dynamics, commitment and shared norms (Zafeiropoulou and Koufopoulos, 2013;Qureshi et al, 2016;Doherty et al, 2009). While social networks within social enterprise ecosystems appear critical as both mediators of stakeholder behaviour and interpretation of logics and discourses (Luhmann, 1989;Van Assche et al, 2014;Hazenberg et al, 2016), the distribution (and potential concentration) of power between stakeholders, as well as stakeholder diversity within the ecosystem, is also an important factor in shaping its development.…”
Section: Conceptualising Social Enterprise Ecosystems Using Evolutionmentioning
confidence: 99%
See 1 more Smart Citation